West African Economic and Monetary Union : Financial Sector Assessment Program-Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2022)
The Financial Sector Assessment Program (FSAP) was conducted amid an economic rebound two years into the COVID-19 pandemic that had a limited impact on the financial sector. Several member states have experienced political instability, with coups in Burkina Faso and Mali leading to economic sanctions for the latter, and an attempted coup in Guinea-Bissau. Yet, short of further political deterioration, economic recovery is expected to persist. The last FSAP was conducted in 2008.